LACK OF DIRECTION DAN PERGESERAN SISTEM PENGENDALIAN MANAJEMEN DALAM ERA PANDEMI COVID-19 - Fidelis Arastyo Andono; Viona Agnita Kristie; William Kurniawan (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2022)
The purpose of this research is to deeply investigate the phenomenon of control problems changes during the pandemic COVID-19 era of crisis that triggers the changes in the organisation’s management control system (MCS). The deep process of control problems changes and the undertaking of MCS in the operational areas of the family business company are the focus of this research. This study is designed as a qualitative case study research that were drawing the data from two family business companies in the culinary business to get the empirical data. The research findings show the fact that lack of directions have become more significant control problems during the crisis era. Based upon the two investigated cases, the crisis era has changed not only the business environment but the business process as well that have led to the changing in the working environment. New problems emerged as the response to the changing of the operational activities and the existing MCS dominated with centralised informal control mechanism could not address it well. These mechanisms could not provide clear guidance for the managers and employees in problem solving and decision making in more unpredicted situation during the crisis. Therefore, strengthening and updating the formal controls are imperative in addressing the changes during the crisis of pandemic COVID-19 era